Methionine sulfoxide reductase regulates brain catechol-O-methyl transferase activity. (October 2014) - Moskovitz, Jackob; Walss-Bass, Consuelo; Cruz, Dianne A.; Thompson, Peter M.; Bortolato, Marco
Abstract Catechol-O-methyl transferase (COMT) plays a key role in the degradation of brain dopamine (DA). Specifically, low COMT activity results in higher DA levels in the prefrontal cortex (PFC), thereby reducing the vulnerability for attentional and cognitive deficits in both psychotic and healthy individuals. COMT activity is markedly reduced by a non-synonymous single-nucleotide polymorphism (SNP) that generates a valine-to-methionine substitution on the residue 108/158, by means of as-yet incompletely understood post-translational mechanisms. One post-translational modification is methionine sulfoxide, which can be reduced by the methionine sulfoxide reductase (Msr) A and B enzymes. We used recombinant COMT proteins (Val/Met108) and mice (wild-type (WT) and MsrA knockout) to determine the effect of methionine oxidation on COMT activity and COMT interaction with Msr, through a combination of enzymatic activity and Western blot assays. Recombinant COMT activity is positively regulated by MsrA, especially under oxidative conditions, whereas brains of MsrA knockout mice exhibited lower COMT activity (as compared with their WT counterparts). These results suggest that COMT activity may be reduced by methionine oxidation, and point to Msr as a key molecular determinant for the modulation of COMT activity in the brain. The role of Msr in modulating cognitive functions in healthy individuals and schizophrenia patients is yet to be determined.